Rheological Characterization of Minerals - Kumawat, Nitin (My University, 2015)
In the present study rheological behaviour and characterization of minerals are investigated by using Anton Paar RheolabQC rheometer to generate extensive rheological data. Four types of minerals viz. iron ore (hematite), zinc ore, iron ore (magnetite) and lime were taken for investigation. The particle size distribution, pH, Scanning Electron Microscopy (SEM) analysis, Energy Dispersive Spectroscopy (EDS) etc. was studied using various bench scale test with standard procedure. The rheology of mineral suspension with the variation of solids concentration, temperature, and fraction of coarse particles are performed. The rheological data shows that upto 30% solid concentration, mineral suspension shows Newtonian behaviour and beyond this shows non-Newtonian behaviour. The rheological investigation of the finner particulate of mineral suspension of iron ore (hematite) and zinc ore slurry is also carried out with the addition of coarser particulate. It is observed that viscosity of both mineral suspension are improved. The temperature effect on the rheological properties of mineral suspension also studied. The rheological data obtained was used to evaluate the pressure drop of mineral ore slurry flowing through straight pipe. It is found that for mineral slurry flowing through pipeline the pressure drop increases with increase in velocity and solid concentration.
ME, MED
Keywords: RHEOLOGICAL; MINERALS; MED